Orange for the Sunsets - Athaide, Tina (New York, NY Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2019)
In alternating voices, friends Asha and Yesofu, one Indian and one African, find their world turned upside-down when Idi Amin decides to expel Asian Indians from Uganda in 1972.
Keywords: Amin, Idi, -- 1925-2003 -- Juvenile fiction; Amin, Idi, -- 1925-2003 -- Fiction; Friendship -- Juvenile fiction; Social classes -- Juvenile fiction; East Indians -- Juvenile fiction; Families -- Juvenile fiction; Forced migration -- Juvenile fiction; Friendship -- Fiction; Social classes -- Fiction; Ethnic relations -- Fiction; East Indians -- Fiction -- Uganda; Family life -- Fiction -- Uganda; Forced migration -- Fiction -- Uganda; Uganda -- Juvenile fiction -- History -- 1971-1979; Uganda -- Fiction -- History -- 1971-1979